2014
DOI: 10.1371/journal.pone.0098677
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Responses to Elevated Temperature in Low and High Elevation Populations of Three Grassland Species

Abstract: Local persistence of plant species in the face of climate change is largely mediated by genetic adaptation and phenotypic plasticity. In species with a wide altitudinal range, population responses to global warming are likely to differ at contrasting elevations. In controlled climate chambers, we investigated the responses of low and high elevation populations (1200 and 1800 m a.s.l.) of three nutrient-poor grassland species, Trifolium montanum, Ranunculus bulbosus, and Briza media, to ambient and elevated tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 114 publications
1
30
1
Order By: Relevance
“…This pattern contrasts with expectations of previous studies, predicting and, in some cases, confirming that plants from extreme environments at higher elevations tend to be less plastic (e.g. Emery, Chinnappa & Chmielewski ; Eranen & Kozlov ; Frei, Ghazoul & Pluess ). All these studies only worked along elevational gradients, and did not explicitly test the effect of different climatic variables.…”
Section: Discussioncontrasting
confidence: 99%
“…This pattern contrasts with expectations of previous studies, predicting and, in some cases, confirming that plants from extreme environments at higher elevations tend to be less plastic (e.g. Emery, Chinnappa & Chmielewski ; Eranen & Kozlov ; Frei, Ghazoul & Pluess ). All these studies only worked along elevational gradients, and did not explicitly test the effect of different climatic variables.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple studies have reported significant P × E for a wide suite of plant functional traits, particularly focusing on the adaptive role of plasticity for populations of specific life‐forms or ecoregions (see e.g., Matesanz & Valladares, and references therein; Bansal, Harrington, et al, ; Frei, Ghazoul, & Pluess, ; Wadgymar, Cumming, & Weis, ). Some studies have also discussed the sources of bias in estimates of population differentiation, including the difficulty in distinguishing genetic from plastic components of such differentiation (Merilä & Hendry, ), the effect of the experimental approach (Gibson, Espeland, Wagner, & Nelson, ) and the role of maternal effects (Bischoff & Müller‐Schärer, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining perennial grassland species (including Trifolium , Ranunculus , and Briza ), a low level of morphological plasticity in alpine species compared to mid‐elevation species was interpreted in terms of an increased level of canalization of traits in harsher conditions (Frei et al. ). However, the common Brachyscome we tested, which were also found in lowland environments, did not have consistently higher plasticity.…”
Section: Discussionmentioning
confidence: 99%